Global PhD Programme in Public Health Sciences boosts international collaborative doctoral training. (30th September 2020) - Bauwens, J; Schulze, M; Nocera, S; Flahault, A; Crivelli, L; Walser, A; Künzli, N
Abstract: Background: The Swiss School of Public Health's (SSPH+) Global PhD Programme in Public Health Sciences (GlobalP3HS) is a doctoral programme, promoting transnational education and mobility co-funded by the European Union's Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No 801076. Students from abroad absolve a PhD training at one of the 12 SSPH+ partner universities in Switzerland. Objectives and Methods: GlobalP3HS aims to train the next generation of public health leaders in both the academic and non-academic sector. Specific attention was given to PhD studies under the "sandwich model" (SM) which fosters research of students from low/middle income countries (LMIC) conducting LMIC-relevant PhD studies in collaboration with an LMIC-based academic institution. The SM targets at increasing chances for LMIC-based postdoctoral careers. The five year programme (October 2018 to September 2023) provides 42-months fellowships to profit from PhD programmes at a Swiss university. Top-scoring candidates were selected in a transparent, merit-based procedure by an international jury, considering students' background and motivation; innovation; methodological quality; public health relevance; and feasibility of the proposed research. Results: Out of 342 valid applications, the jury scored 147 as eligible (score 8-10). In total, 53 students (31 women) were successful in matching up with co-funding supervisors. PhD-students from 31 countries representing all global regions, including 21 PhD under the SM, are enrolled at seven Swiss SSPH+ partner universities. Conclusions: GlobalP3HS is an innovative solution to strengthen global research collaborations. The SM abates "brain drain" as it clears the path for successful careers in LMICs, where graduates become change makers capitalising on solid academic collaborations with the SSPH+ network. Key messages: GlobalP3HS trains PhD fellows in public health sciences to become change-making leaders in academic institutions and public health organisations. GlobalP3HS is an initiative from the Swiss School of Public Health strengthening equitable, fair, balanced, and innovative inter-university and global partnerships.